Effect of radius of fillet on shear stress for cylindrical shaft - Norsyazwani, Badilah (2012)
This project presents an investigation effect of the radius of the fillet on shear stress for cylindrical shaft by using finite element analysis. The shaft has the tendency to fail due to the inappropriate design of fillet radius. Hence, the best models need to design. 18 models were constructed with different ratio two diameters shaft and radius of fillet in SOLIDWORK. These models imported into PATRAN software to analyze the models with different given of the value of torque. In order to simulate torque, MPC RBAR was employed on model. AISI 4130 was selected material for all models. The value for Young Modulus of Elasticity = 206GPa and the Poisson Ratio = 0.3 was used in this analysis. The stress concentration factor was determined to compare the simulation result and equation. As expected, result showed that increased the radius of fillet of shaft reduced the value of shear stress. The ratio of two diameters shaft 1.09 was the best design compared to others because all cases produced the lowest value of shear stress. The value of shear stress was increase when the torque given was increased.